2021
DOI: 10.1017/s0025315421000618
|View full text |Cite
|
Sign up to set email alerts
|

More than local adaptation: high diversity of response to seawater acidification in seven coral species from the same assemblage in French Polynesia

Abstract: Responses of corals to seawater acidification have been extensively studied. Sensitivity varies widely between species, highlighting the need to avoid extrapolation from one to another to get an accurate understanding of coral community responses. We tested the responses of seven coral species (Acropora cytherea, Acropora hyacinthus, Acropora pulchra, Leptastrea pruinosa, Montipora grisea, Pavona cactus, Pocillopora verrucosa) from the Mo'orea lagoon to a 48-day exposure to three pH scenarios (pH 7.95, 7.7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
1
1
0
Order By: Relevance
“…In our study, calcification and surface growth decreased in all species under OA, which is consistent with previous findings (e.g., Sekizawa et al 2017) and the generalised effect of OA on coral calcification (Kornder et al 2018). Still, calcification in Acropora cytherea may be unaffected by OA at stable and even higher pCO2 than tested here (1,000 µatm pCO2; Godefroid et al 2021). Likewise, Pocillopora verrucosa maintained stable calcification rates with moderately and highly elevated pCO2 under stable pH conditions (700 and 1,000 µatm pCO2; Comeau et al 2019b).…”
Section: Decreased Growth Under Ocean Acidification With Diel Ph Osci...supporting
confidence: 93%
“…In our study, calcification and surface growth decreased in all species under OA, which is consistent with previous findings (e.g., Sekizawa et al 2017) and the generalised effect of OA on coral calcification (Kornder et al 2018). Still, calcification in Acropora cytherea may be unaffected by OA at stable and even higher pCO2 than tested here (1,000 µatm pCO2; Godefroid et al 2021). Likewise, Pocillopora verrucosa maintained stable calcification rates with moderately and highly elevated pCO2 under stable pH conditions (700 and 1,000 µatm pCO2; Comeau et al 2019b).…”
Section: Decreased Growth Under Ocean Acidification With Diel Ph Osci...supporting
confidence: 93%
“…This overall response to low pH was different to the one observed in P. lutea and could potentially be related to the morphological differences between these two species. However, similar calcification responses to OA have been found between mounding and branching morphologies (Comeau et al, 2014b) and both mounding and branching species have shown stronger impacts in multispecies comparisons (e.g., Brown and Edmunds, 2016;Godefroid et al, 2021). Instead, a potential explanation might be that P. cylindrica responds to low pH with a 'hibernation strategy'.…”
Section: Discussionmentioning
confidence: 68%